A fully distributed deployment algorithm for underwater strong k-barrier coverage using mobile sensors. (April 2019) - Shen, Weiqiang; Zhang, Chuanlin; Zhang, Xiaona; Shi, Jinglun
Sensor barrier coverage has been recognized as an appropriate coverage model for intrusion detection, and many achievements have been obtained in two-dimensional terrestrial wireless sensor networks. However, the achievements based on two-dimensional assumption cannot be directly applied in three-dimensional application scenarios, for example, underwater wireless sensor networks. In this article, we aim to devise a fully distributed deployment algorithm for constructing maximum-level underwater strong k -barrier coverage with available mobile sensors in underwater environment to satisfy the requirement of underwater security-related applications. We first analyze how to form underwater strong one-barrier coverage with minimum mobile sensors, based on which we obtain the minimum number of sensors required for constructing underwater strong one-barrier coverage and the corresponding optimal final positions of these sensors. Then, we propose a fully distributed deployment algorithm for constructing maximum-level underwater strong k -barrier coverage with available mobile sensors in three-dimensional underwater environment. We show that the proposed algorithm has a guaranteed termination after a finite time and is able to self-heal the underwater strong k -barrier coverage to deal with sudden sensor failures. Experimental results validate our analysis and show that the proposed algorithm outperforms both Hungarian and HungarianK in terms of duration and achieves performance close to them with respect to several performance metrics.